Splendour in the seas - Yahya, Harun, 1956-; Okur Production (Istanbul : Okur Production, 2000)
This film discovered obout the underwater world. Audience will be amazed at God's art of creation.
Contents on videodisc: Introduction; Defence tactics; Shape changing; Symbiosis; The evolution misconeption
Keywords: Seafaring life -- Religious aspects -- Islam; Seafaring life; Creation (Islam).